Eco-industrial parks construction and industrial chain resilience - Zhang, Huan; Xu, Bo (Frontiers in Sustainable Cities, 2025)
This article explores the impact of eco-industrial park construction from the perspective of industrial chain resilience. Eco-Industrial Parks (EIP) help reduce environmental pollution and make the industrial sector more environmentally friendly, representing the direction of sustainable industrial development. Based on panel data from 285 cities from 2006 to 2023, this article uses the difference in differences method to explore the impact of the construction of national eco-industrial demonstration parks on industrial chain resilience. Research has found that in pilot cities, EIP has made a positive contribution of 1.56 to 2.75% in improving industrial chain resilience. Considering the exclusion of provincial capitals and other policy factors, the impact of EIP is robust. Compared to the eastern region, the role of EIP in enhancing the industrial chain is more pronounced in the central and western regions. Meanwhile, in regions with higher levels of regional integration, there is a stronger positive impact. The industrial structure upgrading caused by green technology innovation and the crowding out effect of high pollution manufacturing industry helps to explain these mechanisms. Further estimates indicate that considering the spatial correlation of various factors, EIP has a significant positive spatial spillover effect on the industrial chain.